Food processing: strategies for quality assessment - Erginkaya, Zerrin; Ahmad, Saghir; Erten, Hüseyin; Malik, Abdul (Food Engineering Series,, 2014)
The aim of food processing is to ensure the microbiological and chemical safety of foods, adequate nutrient content and bioavailability and acceptability to the consumer with regard to sensory properties and ease of preparation. Processing may have either beneficial or harmful effects on these properties, so each of these factors must be taken into account in the design and preparation of foods. This book offers a unique look at the subject and provides not only an update of state-of-the art techniques in many critical areas of food processing and quality assessment, but also the development of value added products from food waste, safety and nanotechnology in the food and agriculture industry and looks into the future by defining current obstacles and future research goals. This book is not intended to serve as an encyclopedic review of the subject. However, the various chapters incorporate both theoretical and practical aspects and may serve as baseline information for future research through which significant development is possible.